2023
DOI: 10.3389/fonc.2023.1044098
|View full text |Cite
|
Sign up to set email alerts
|

Occult hepatitis B in patients with cancer during immunotherapy with or without chemotherapy: A real-life retrospective single-center cohort study

Abstract: IntroductionFew data about the safety of immune checkpoint inhibitors (ICIs) in the patients with solid tumor with Occult Hepatitis B Virus (OBI) are available. According to the Taormina Workshop on Occult HBV Infection Faculty Members we defined as potential-OBI (pOBI) the HBV DNA negativity with anti-hepatitis B core antibody (anti-HBc) positivity (pOBI seropositive), and the patients with HBsAg–negative and anti-HBc–negative and Hepatitis B surface antibody (anti-HBs)–negative are defined pOBI seronegative.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In the treatment of malignant lymphoma also, the higher the value on pretreatment HBc antibody testing, the higher the risk of reactivation in HBs antigen-negative anti-HBc antibodypositive patients [66]. Although immune checkpoint inhibitors (ICIs) have been used for the treatment of many cancers in recent years, as of now, no OBI reactivation due to ICIs has been reported [67,68]. Clarke et al used anti-TNF preparations in 120 HBs antigennegative anti-HBc antibody-positive cases and found that positive conversion of HBs antigen occurred in only one case (0.8%), indicating a low frequency of reactivation [69].…”
Section: Reactivation and Seroconversion During Immunosuppressive Statementioning
confidence: 99%
“…In the treatment of malignant lymphoma also, the higher the value on pretreatment HBc antibody testing, the higher the risk of reactivation in HBs antigen-negative anti-HBc antibodypositive patients [66]. Although immune checkpoint inhibitors (ICIs) have been used for the treatment of many cancers in recent years, as of now, no OBI reactivation due to ICIs has been reported [67,68]. Clarke et al used anti-TNF preparations in 120 HBs antigennegative anti-HBc antibody-positive cases and found that positive conversion of HBs antigen occurred in only one case (0.8%), indicating a low frequency of reactivation [69].…”
Section: Reactivation and Seroconversion During Immunosuppressive Statementioning
confidence: 99%
“…In our retrospective cohort study, we evaluated 150 potential-OBI (pOBI) patients (HbsAg negative) without HBV prophylaxis during immunotherapy. Only one pOBI patient (anti-Hbc+, anti-Hbs+ and anti-Hbe−) showed an increase in ALT (>3× ULN) with concomitant transient detectability of HBV-DNA [74]. Lin and colleagues demonstrated that seropositive HBsAg (OR = 6.30, p = 0.020), the existence of liver involvement (OR = 2.10; p = 0.030), and detectable baseline HBV DNA levels (OR = 2.39, p = 0.012) were risk factors for any-grade hepatotoxicity during ICIs, while the prophylactic antiviral therapy decreased hazard for the incidence of grade 3-4 hepatotoxicity (OR = 0.10, p = 0.016) [75].…”
Section: Viral Diseasesmentioning
confidence: 99%
“…Table 3 summarizes the data on HBV reactivation in patients receiving ICIs[ 126 - 129 ]. The rate of HBV reactivation among HBsAg-positive cancer patients is 0.5% to 5.3% during ICI therapy.…”
Section: Risk Factors For Hepatitis B Reactivationmentioning
confidence: 99%